Clinical Outcomes of Golimumab as First, Second or Third Anti-TNF Agent in Patients with Moderate-to-Severe Ulcerative Colitis. Issue 8 (30th June 2017) - Taxonera, Carlos; Rodríguez, Cristina; Bertoletti, Federico; Menchén, Luís; Arribas, Julia; Sierra, Mónica; Arias, Lara; Martínez-Montiel, Pilar; Juan, Alba; Iglesias, Eva; Algaba, Alicia; Manceñido, Noemí; et al.
Abstract : Background: Golimumab efficacy data in ulcerative colitis (UC) are limited to anti–tumor necrosis factor α (TNF)-naive patients. The aim of this study was to assess the short-term and long-term efficacy of golimumab used as first, second, or third anti-TNF in UC in a real-life clinical setting. Methods: This retrospective multicenter cohort study included patients with moderate-to-severe UC treated with golimumab. The primary efficacy endpoints were short-term partial Mayo score response, long-term golimumab failure-free survival, and colectomy-free survival. Results: In 142 patients with UC, golimumab was administered as first (40%), second (23%), or third anti-TNF (37%). Ninety-two patients (65%, 95% confidence interval 56.6–73) achieved short-term clinical response. Forty-five patients (32%, 95% confidence interval 23.7–39.7) achieved clinical remission. Response rates for golimumab were 75% as first anti-TNF, 70% as second anti-TNF (ns versus first anti-TNF), and 50% as third anti-TNF ( P = 0.007 versus first anti-TNF). After 12 months median follow-up (interquartile range 6–18), 60 patients (42%, 95% confidence interval 34–51) had golimumab failure, and 15 patients (11%) needed colectomy. Thirty-one patients (22%) needed golimumab dose escalation, and 71% of these regained response after escalation. Starting maintenance with 100 mg golimumab doses and short-term nonresponse were independent predictors of golimumab failure. Conclusions: In this real-life cohort of patients with UC, golimumab therapy was effective for inducing and maintaining clinical response. Although anti-TNF–naive patients had better outcomes, golimumab was also effective in anti-TNF–experienced patients. Only the patients given golimumab after previous failure of 2 anti-TNF agents had significantly worse outcomes. Golimumab dose escalation was beneficial and safe.